Porang (Amorphophallus oncophyllus) tuber extract improved the histopathological features of diabetic rat (Rattus norvegicus) testicles - Dwi Puspa Sukma Viranda; Rochmah Kurnijasanti; Kadek Rachmawati; Iwan Sahrial Hamid; Pudji Srianto; Hani Plumeriastuti; Lita Rakhma Yustinasari (Universitas Airlangga, 2024)
This study aims to determine the effect of porang (Amorphophallus oncophyllus) tuber extract on the histopathological features of the testicle of alloxan induced rats (Rattus norvegicus). Thirty male rats were randomly divided into six groups. Rats in group C- were injected with distilled water, while rats in groups C+, T0, T1, T2, and T3 were injected with 120 mg/kg bw alloxan. Blood glucose was measured three days after alloxan injection. Rats in groups C- and C+ were then administered with 1% Na-CMC, whereas rats in groups T0, T1, T2, and T3 were then administered with 45mg/kg bw metformin, and 100, 200, and 400 mg/kg bw of porang tuber extract, respectively. All solution were given orally once every day for 14 days. Spermatogenic activity was assessed using the Johnsen scoring system and analyzed by Kruskal-Wallis, followed by the Mann-Whitney test. The diameter and epithelial thickness of the seminiferous tubule were measured using image raster software and analyzed using Anova followed by Duncan's test. The results showed that spermatogenesis score, diameter, and epithelial thickness of seminiferous tubule of group C+ were smaller (p <0.05) than group C-. Spermatogenesis scores of groups T0, T1, T2, and T3 were higher (p <0.05) than group C+. Seminiferous tubule diameter and epithelial thickness in groups T0, T1, and T2 were greater (p <0.05) than group C+. It could be concluded that porang tuber extract at a dose of 200 mg/kg bw improved the spermatogenesis score, diameter seminiferous tubule, and thickness of the epithelium of diabetic rats.